The complete mitochondrial genome of the Papilio memno (Lepidoptera:Papilionidae). Issue 3 (2nd July 2020) - Shi, Min-Rui; Yu, Hong; Xu, Jin
Abstract: In this study, the mitochondrial genome (mitogenome) sequence of Papilio memno is determined using next-generation sequencing. The entire mitogenome genome is determined to be 15, 262 bp in length. It contains 37 genes, including 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs), and an adenine (A) + thymine (T)-rich region. The overall GC content of the genome is 20.3%. A phylogenetic tree reconstructed by 39 mitochondrial genomes reveals that P. domestica is most closely related to Prunus salicina .